Organizational Communication and Spiritual Intelligence as Predictors Of Organizational Conflict Management Styles Among Pastors of the Evangelical Christian Church in Timor - Yanti Florida Silopo; Susana Prapunoto; Sutarto Wijono (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The purpose of this study is to test organizational communication and spiritual intelligence simultaneously as a predictor of organizational conflict management style in pastors of the Evangelical Church in Timor (GMIT). This study is a quantitative research, with multiple regression analysis techniques. The data collection technique was carried out using the Rahim Organizational Conflict Inventory II from Rahim & Magner (1995) measuring the integrative dimension and the distributive dimension. The results of the partial findings also show that spiritual intelligence has an effect on organization conflict management styles in GMIT pastors. In addition, it is concluded that the existence or absence of the use of conflicts management styles among male and female pastors cannot use the gender variable as determining things. The findings may inform training programs for pastors and have practical implications for improving leadership practices and fostering a harmonious environment within religious organizations.